A review of CRISPR-Cas and PCR-based methods for the detection of animal species in the food chain-current challenges and future prospects - Sultana, Sharmin; Azlan, Azrina; Mohd Desa, Mohd Nasir; Mahyudin, Nor Ainy; Anburaj, Amaladoss (Taylor and Francis, 2024)
Regular testing and systematic investigation play a vital role to ensure product safety. Until now, the existing food authentication techniques have been based on proteins, lipids, and nucleic acid-based assays. Among various deoxyribonucleic acid (DNA)-based methods, the recently developed Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) based bio-sensing is an innovative and fast-expanding technology. The CRISPR/Cas-9 is known as Clustered Regularly Interspaced Short Palindromic Repeats due to the flexibility and simplicity of the CRISPR/Cas9 site-specific editing tool has been applied in many biological research areas such as Gene therapy, cell line development, discovering mechanisms of disease, and drug discovery. Nowadays, the CRISPR-Cas system has also been introduced into food authentication via detecting DNA barcodes of poultry and livestock both in processed and unprocessed food samples. This review documents various DNA based approaches, in an accessible format. Future CRISPR technologies are forecast while challenges are outlined.